PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KINERJA TERHADAP PELAYANAN DAN KEPUASAN PASIEN RSUD A.M. PARIKESIT KABUPATEN KUTAI KARTANEGARA - Dhesy Eka Santy; Zainal Ilmi; Aji Sofyan Effendi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The hospital as a public health service organization, serves to serve the wider community in the formof services. From this phenomenon, researchers are interested in conducting a research study on theEffect of Transformational Leadership and Employee Performance on Employee Service and PatientSatisfaction at A.M. Hospital. Parikesit Kutai Kartanegara Regency. The research method is causalassociative research, namely research that intends to describe and test the hypothesis of therelationship between two or more variables. The method used in the study is the path analysis method.Transformational Leadership Style has a significant effect on services at Aji Muhammad ParikestiHospital, Kutai Kartanegara Regency with a significance value of 0.000 and a regression coefficient of1.136. Employee performance has a significant effect on services at Aji Muhammad Parikesti Hospital,Kutai Kartanegara Regency with a significance value of 0.004 and a regression coefficient of 0.889.Transformational Leadership Style is significant on Patient Satisfaction at Aji Muhammad ParikestiHospital, Kutai Kartanegara Regency with a significance value of 0.046 and a regression coefficient of0.180. Employee performance has a significant effect on patient satisfaction at Aji MuhammadParikesti Hospital, Kutai Kartanegara Regency with a significance value of 0.005 and a regressioncoefficient of 0.526.